Patriarchal and Matriarchal Perspectives in Rani Manicka’s the Rice Mother (International Journal of Language, Literacy and Translation, 2025)
Rani Manicka’s The Rice Mother was analysed by employing feminist literary criticism that dwells on the patriarchal and matriarchal aspects presented in the novel. This is to fill the research gap on feminist literary criticism in this respect, focusing on Malaysian English novels. To do so, two objectives are set as (1) to examine the representations of the female characters in the patriarchal society by employing Simone De Beauvoir’s The Second Sex theory and (2) to identify the levels of modern matriarchal society manifested through the protagonist in the novel by employing Goettner-Abendroth’s Levels of Modern Matriarchal Society. A qualitative content analysis (QCA) was used. Using an integrated view of text, the social reality is explored. The results indicate that the female characters in the selected novel vary in the patriarchal context where most females are the victims of the patriarchal society. It was also found that the protagonist proved to be a formidable matriarch through her behaviour in all four levels identified. This study contributes to the analysis of feminist literary criticism in the Malaysian context. It is also deemed beneficial in a broader context as it can provide a voice for women who are still considered as the marginalised other in the society. The study highlights the lack of female representation in popular culture. This study is also deemed crucial to empower women as it can provide a voice for women who are still being considered as the other for the balance of power in society and a strong family as a small social institution.